Stability of nanofluids in quiescent and shear flow fields - Witharana, Sanjeeva (Springer, 2011)
An experimental study was conducted to investigate the structural stability of ethylene glycol-based titanium dioxide nanoparticle suspensions (nanofluids) prepared by two-step method. The effects of particle concentration, fluid temperature, shear rate and shear duration were examined. Particle size and thermal conductivity measurements in quiescent state indicated the existence of aggregates and that they were stable in temperatures up to 60°C. Shear stability tests suggested that the structure of nanoparticle aggregates was stable in a shear interval of 500-3000 s(-1 )measured over a temperature range of 20-60°C. These findings show directions to resolve controversies surrounding the underlying mechanisms of thermal conduction and convective heat transfer of nanofluids.